Eremocoris juquilianus a new bug species from the mountains in Oaxaca, Mexico (Hemiptera: Rhyparochromidae: Drymini): with description of the immature stages - Peredo, Luis Cervantes; Brailovsky, Harry; Santacruz, Jezabel Baez; Brailovsky, Harry; Santacruz, Jezabel Baez (Zootaxa, 2015)
The genus Eremocoris Fieber is represented by 43 species, and three subspecies, 14 and 3 are Palearctic, 5 Oriental, 3 Afrotropical and 21 Nearctic. 14 species are recorded in Mexico. This contribution contains descriptions and illustrations of the adult and all immature stages of Eremocoris juquilianus sp. nov. and notes on its biology, habitat, and distribution in Mexico.